The Effect of Health - Nutrition Education on Health Promotion in Resident Elderly in KAHRIZAK in TEHRAN - Sima Ghasemi; Farshad Sharifi; Shahrbanoo Maghsoodnia; Fariba Teymoori (University of Social Welfare & Rehabilitation Sciences, 2006)
Objectives: Aging is natural course of life which accompanied by changes of metabolism. The exchanges susceptible elderly to malnutrition in researched was do in this back ground about 3-13% of aged population involved to malnutrition that this rate increased to 30-60% in initialized elderly. In this study, we assessed the effects of medical care staff's education on nutritional situation of elderly livid in KAHRIZAK charity Foundation in TEHRAN during 4 months. Methods & Material: 192 elderlies which lived in KCF and equal or older than 65 satisfied in including to this study randomly. (50 males and 142 females) although for inclusion they had not involved to an staged liver and renal disease and had not history of surgery during one months before initiated of study. We checked HB, HCT, LDL, HDL, FBS, CRP, ALB, although assessed MNA, MMSE, ADL, Norton sore before and after educational intervention. Educational workshop operated for medical and nursing staffs of KCF during 3 days. Clinical and Para clinical assessments did 4 months, again, after that, and collected data entered to EXEL and analyzed by SPSS soft wares. Results: Before educational intervention 35.9% of elderly had very sever or severe malnutrition that after intervention decreased to 18.3% mean of ALB, HB, HCT, LDL, F.B.S increased after intervention and significant (p<0/05). Nutritional situation correlated to age, mouth and swallowing disorders, poly pharmacy, cognitive condition, ADL score in eating and Norton scores significant. Conclusion: Base of this findings is concluded medical and nursing staffs nursing homes has significant effects on decrease of moderate and severe malnutrition in elderly. Education in this instated have to continues and not cross over like this study for significant Paraclinical improvements of nutritional indicators.